Effects of Repetitive Transcranial Magnetic Stimulation on Children From 6 to 10 Years of Age With Attention Deficit Hyperactivity Disorder—A Randomized Controlled Trial. - Qian, Yuqian; Lu, Yun; Zhang, Lili; Xu, Ying; Ji, Yingying; Du, Feiyu; Tang, Weifeng; Tao, Yue; Chen, Wenxiang; Chan, Kai Leng Catherine; Yin, Zhifei; Shen, Ying (Physiotherapy Research International, 2025)
Background: Attention deficit hyperactivity disorder (ADHD) is one of the most prevalent neurodevelopmental disorders, with an estimated prevalence of 5.6% among Chinese children. This population needs to seek novel non‐pharmacological alternatives for treatment. Objective: This research explored the effects of 6‐week high‐frequency repetitive transcranial magnetic stimulation (rTMS) on clinical symptoms and executive function in children from 6 to 10 years with ADHD. Methods: Forty‐eight children diagnosed with ADHD were randomly allocated to either the treatment group (n = 24) or the control group (n = 24). The control group received behavioral parent training and sham rTMS protocol, while the treatment group received behavioral parent training for children and rTMS treatment. High‐frequency rTMS (10 Hz) was applied to the right dorsolateral prefrontal cortex (DLPFC) for 30 min per session, three times per week, totally for six continuous weeks. The Swanson, Nolan and Pelham‐IV rating scale (SNAP‐IV), the integrated visual and auditory continuous performance test (IVA‐CPT), the n‐back task (1‐back) and the Word‐color Stroop task were all utilized to evaluate clinical symptoms and executive functions before and after six‐week treatment. Results: Finally, a total of 43 (89.6%) participants attended all study sessions, with 1 patient in the treatment group and 4 patients in the control group dropped out, respectively. At post‐treatment, the scores of attention deficit, hyperactivity‐impulsivity, and oppositional defiance factors in the SNAP‐IV were all significantly decreased compared with the baseline data in both groups (all p < 0.01), while the differences in attention deficit scores for the treatment group were significantly greater than the control group (p = 0.04). In addition, compared with pre‐treatment, the comprehensive control quotient in the IVA‐CPT was significantly increased in the treatment group (p = 0.01). Conclusion: High‐frequency rTMS targeting the right DLPFC can effectively improve the clinical symptoms of attention deficit in young children with ADHD.